Decomposition based least squares iterative estimation algorithm for output error moving average systems. Issue 4 (2014) - Wenge Zhang
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to solve the heavy computational problem of parameter estimation algorithm. Design/methodology/approach – Presents a decomposition least squares based iterative identification algorithm. Findings – Can estimate the parameters for linear or pseudo‐linear systems and have lower computational burden. Originality/value – This paper adopts a decomposition technique to solve engineering computation problems and offers a potential and efficient algorithm. <ack> <x xml:space="preserve"> Acknowledgements </x> This work was supported by the National Natural Science Foundation of China. </ack>